2019
DOI: 10.1016/j.aott.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with needle breakage of antegrade suture passer and effect of intratendinous remnant needle tip on clinical outcomes after arthroscopic rotator cuff repair

Abstract: Objective The aim of this study was to evaluate factors associated with the needle breakage of antegrade suture passer and the effect of intratendinous remnant needle tip on clinical outcomes after rotator cuff repair. Methods We retrospectively reviewed 283 patients (138 men and 145 women; mean age: 59.7 ± 9.3 years) who underwent arthroscopic repair for full-thickness rotator cuff tear. We evaluated the characteristics of 16 patients in whose needle tip had been broke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The incidence of a broken needle or needle breakage is not unknown. Broken needles have been reported during dental procedures [ 2 , 3 ], laparoscopy [ 4 ], surgical operation [ 1 ], percutaneous needle biopsy [ 5 ], endobronchial ultrasound-guided-transbronchial needle aspiration [ 6 ], antegrade suture passer of shoulder [ 7 ], bone biopsy [ 8 ], acupunctures [ 9 ], spinal anesthesia [ 10 , 11 ], and the injection of drugs [ 12 , 13 ]. Seven case reports of broken needles during various procedures were reported in 2021 from a PubMed ® search.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of a broken needle or needle breakage is not unknown. Broken needles have been reported during dental procedures [ 2 , 3 ], laparoscopy [ 4 ], surgical operation [ 1 ], percutaneous needle biopsy [ 5 ], endobronchial ultrasound-guided-transbronchial needle aspiration [ 6 ], antegrade suture passer of shoulder [ 7 ], bone biopsy [ 8 ], acupunctures [ 9 ], spinal anesthesia [ 10 , 11 ], and the injection of drugs [ 12 , 13 ]. Seven case reports of broken needles during various procedures were reported in 2021 from a PubMed ® search.…”
Section: Discussionmentioning
confidence: 99%
“…The potential reasons for needle detachment could be syringe defects, fault in handling by the operator, or the patient. Risk factors associated with needle breakage of antegrade suture passer are thicker tendon, higher tendinosis, and delaminated tears [ 7 ]. Saurin et al reported that emergency procedures, morbid obesity and multiple puncture attempts, redirection without introducer, poorly differentiated landmarks, and resistance to needle advancement increase the risk of a broken needle during spinal anesthesia [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is too late for the postoperative observation of broken needle tips, and reoperation is unacceptable for patients and may result in more serious injuries in patients, which is also a source of medical dispute. A few literature studies have discussed about the suture passer needle breakage issue recently (9)(10)(11)(12)(13). The phenomenon of a broken suture passer needle was first described by Song and Ramsey in a case report in 2008 (11).…”
Section: Introductionmentioning
confidence: 99%
“…However, the notch at the tip of the needle often causes problems during the surgery. When the needle tip penetrates through thick tendon or the acromion in the narrow subacromial space, the needle is vulnerable to break at the notch site ( 9 ). Broken needle tips are tiny metal pieces, so that they cannot be observed easily during surgery and can only be identified by postoperative radiography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation